Cyber Tuition Saujana Utama Management System - Harun, Muhammad Azri Ishraf; Selamat, Norhanim (Applied Information Technology And Computer Science, 2023)
Cyber Tuition Saujana Utama Management System is designed to efficiently manage all information related to tuition centers. Currently, the system relies on manual processes involving Microsoft Word software, where data is printed and stored in separate files. However, there is a lack of a dedicated system to manage important data specific to the tuition center. This system offers online registration for new students, allowing them to submit their applications electronically. To streamline attendance tracking, QR code scanning is implemented, eliminating the need for manual attendance forms. Additionally, the system incorporates payment gateway technology, enabling students to make tuition fee payments directly. The chosen methodology for system development is the prototype model. The system being developed is web-based and uses HTML, CSS and JavaScript programming languages to create a user-friendly interface. This system is anticipated to be successfully developed, efficiently managing all user operations, and effectively replacing the current manual system with a more systematic and modernized one.